Liver-mediated shedding of platelet GPVI - Berndt, Michael; Andrews, R. (American Society of Hematology, 2016)
The in vivo mechanisms underlying antibody-based shedding of the key platelet collagen receptor glycoprotein VI (GPVI) are potentially significant for future antibody-based thromboprotective agents. In this issue of Blood, Stegner et al reveal how the inhibitory Fc receptor, Fc g RIIB, on mouse liver sinusoidal endothelium mediates both antibody-induced GPVI shedding and entrapment of platelets in the liver.